Economic and Social Activeness as Determinants of Local Development in Mazovieckie Voivodeship (Poland) - Pomianek, Iwona (Olsztyn Economic Journal, 2018)
The aim of the research was to recognise the correlation between economic and social activeness and the local development level of semi-urban and rural gminas in Mazovieckie Voivodeship. The analysis shows that demography and the condition of infrastructure are strongly correlated to economic activeness, the number of businesses and the unemployment rate. On the other hand, social determinants (the number of NGOs, electoral turnout or the local government’s predispositions) also play a role. About 70% of both semi-urban and rural gminas remained in the 1st Classes of the G-ranking and in the SA-ranking at the same time. For the 1st Classes of the G-ranking and EA-ranking this participation was even higher – from 80% for rural units to almost 90% for semi-urban gminas. Being located in close proximity to a city is an important growth stimulant for suburban gminas. More than 80% of highly developed units in the G-ranking were located in the Warsaw Metropolitan Area. Furthermore, there were no suburban gminas near the capital in the lowest development group. A low level of both economic and social activeness characterized only rural peripheral gminas.